2011
DOI: 10.1007/s11465-011-0123-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostriction varieties and stress relief caused by pulsed magnetic field

Abstract: Magnetostriction is investigated to evaluate the stress relief caused by pulsed magnetic field treatment, because this physical property is closely associated with residual stress. Magnetostriction of different stressed samples is measured in this paper. The stress variations caused by pulsed magnetic treatment are also compared. It is found that magnetostriction variations are closely associated with stress changes. Thermodynamic potential is used to find the relationship between them. Based on several assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Similar results were also reported in the 30CrMnSiA steel [35]. Further, the extent of the relaxation effect also correlates to the direction of the magnetic field [95][96][97]. Specifically, the effect was most efficient when the magnetic field was perpendicular to the direction of the principle stress, while it was relatively small when they were parallel [95].…”
Section: Frictionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were also reported in the 30CrMnSiA steel [35]. Further, the extent of the relaxation effect also correlates to the direction of the magnetic field [95][96][97]. Specifically, the effect was most efficient when the magnetic field was perpendicular to the direction of the principle stress, while it was relatively small when they were parallel [95].…”
Section: Frictionsupporting
confidence: 74%
“…Despite the previous research which revealed that the magnetostriction effect was not the sole factor [37], the directionality of the effect of the PMT indicates that the magnetostriction effect does play a role in the process of residual stress relaxation. In addition, a new method has been proposed to predict the degree of residual stress relaxation according to the magnitude of the magnetostriction coefficient [97].…”
Section: Frictionmentioning
confidence: 99%
“…Therefore, it is very important to study the coupling law of the three energy fields (thermal-TEMCP -deformation) in electromagnetic coupling. Cai et al [26] found that the product of the magnetostriction amplitude and the stress magnitude is nearly a constant during the magnetic field treatment. The removal of the residual stress in metal can improve the mechanical properties.…”
Section: Discussion Of Temcp Mechanismmentioning
confidence: 99%
“…However, the mechanisms of residual stress release by electromagnetism have only been explained qualitatively. Cai et al [33] found that magnetostriction variations had a close association with changing of the state of the stress and were valuable for the optimization of the processing parameters and evaluation of stress relief. Hou et al [31] revealed that at lower magnetic fields (for instance, 1.0 T and 1.3 T), the dislocation…”
Section: Introductionmentioning
confidence: 99%
“…It was evident that the mechanisms how these fields actually influence the material stress states quantitively were unclear. Thus, numerical modeling of the electromagnetic fields and mechanical fields was developed in order to develop better understanding of the residual stress reduction mechanisms [33][34][35], considering two treatment methods -coupled electromagnetic treatment and pulsed magnetic field treatment.…”
Section: Introductionmentioning
confidence: 99%